Genetic Risk Assessments in Individuals at High Risk for Inherited Breast Cancer in the Breast Oncology Care Setting - Pal, Tuya (2012)
BACKGROUND: It has become increasingly common to consider BRCA mutation status when determining optimal cancer risk management and treatment options in order to improve patient outcomes. Knowledge about the risk for hereditary cancer at or as close as possible to the time of diagnosis allows patients access to the most risk reduction options available. METHODS: This paper illustrates the role of genetic risk assessment for hereditary breast cancer, using hereditary breast and ovarian cancer (HBOC) syndrome as a model due to germline mutations in the BRCA1 and BRCA2. Specifically, the value of genetic counseling and testing for HBOC across the cancer prevention and control continuum is outlined as it pertains to breast cancer. RESULTS: In recognition of the importance of risk assessment for hereditary breast cancer, leading health professional organizations have developed specific guidelines and recommendations to providers for identification of women at increased risk for carrying a BRCA mutation. CONCLUSIONS: Institutional efforts specific to genetic counseling and testing have resulted in the implementation of a model driven by physician recommendation as a referral system for high-risk breast cancer patients. Establishing an infrastructure to support research, education, and outreach initiatives focused on BRCA genetic counseling and testing will provide information that can improve the delivery of cancer genetics services.